1995
DOI: 10.1093/hmg/4.10.1967
|View full text |Cite
|
Sign up to set email alerts
|

A gene for autosomal dominant nonsyndromic hereditary hearing impairment maps to 4p16.3

Abstract: Mapping genes for nonsyndromic hereditary hearing impairment may lead to identification of genes that are essential for the development and preservation of hearing. We studied a family with autosomal dominant, progressive, low frequency sensorineural hearing loss. Linkage analysis employing microsatellite polymorphic markers revealed a fully linked marker (D4S126) at 4p16.3, a gene-rich region containing IT15, the gene for Huntington's disease (HD). For D4S126, the logarithm-of-odds (lod) score was 3.64 at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 38 publications
2
57
0
Order By: Relevance
“…A telomeric boundary of the disease locus was estimated to be between D4S2366 and D4S2935 by another recombination observed in individual III-17. These results, with reference to previously reported data for DFNA6/14 (Lesperance et al 1995;Van Camp et al 1999), suggested that the disease of this family was associated with a new LFSNHL locus between D4S2366 and D4S2983. No mutations were found in the ten genes other than WFS1 analyzed.…”
Section: Genetic Findingssupporting
confidence: 88%
See 2 more Smart Citations
“…A telomeric boundary of the disease locus was estimated to be between D4S2366 and D4S2935 by another recombination observed in individual III-17. These results, with reference to previously reported data for DFNA6/14 (Lesperance et al 1995;Van Camp et al 1999), suggested that the disease of this family was associated with a new LFSNHL locus between D4S2366 and D4S2983. No mutations were found in the ten genes other than WFS1 analyzed.…”
Section: Genetic Findingssupporting
confidence: 88%
“…The mutation site in the hydrophobic, extracytoplasmic, juxta-transmembrane region seen in this family was hitherto undescribed. This unique mutation site in our patients may be related to their milder phenotype compared with those of the six previously identified DFNA6/14 patients with WFS1 mutations (Lesperance et al 1995;Strom et al 1998). It is likely that a genotype-phenotype correlation is also applicable in the case of this disorder.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Based on the audiometric configurations, we screened for the presence of TECTA and WFS1 mutations. Exons 17,18,19, and 20 of TECTA, corresponding to the zona pellucida domain of alpha-tectorin (the product of TECTA), were amplified by polymerase chain reaction (PCR), because mutations in that region lead to autosomal dominant mid-frequency SNHL. 6 The entire coding regions of WFS1 were amplified as previously described.…”
Section: Genetic Analysismentioning
confidence: 99%
“…Selective neuronal loss in the neostriatum and cortex causes choreic movement and dementia (Ross et al, 1997). The gene defective in HD is located on chromosome 4p16.3 (Lesperance et al, 1995) and is translated into huntingtin, a 350 kDa ubiquitous protein (Ide et al, 1995;Sharp et al, 1995). Moreover, increased CAG trinucleotide repeats in exon 1 lead to polyglutamine expansion in the N-terminus of huntingtin and are responsible for neurodegeneration in the HD brain (MacDonald et al, 1993, The Huntington's Disease Collaborative Research Group).…”
Section: Introductionmentioning
confidence: 99%